The Effect of Counseling with Animation Media on Increasing Knowledge of Anemia in Young Women at SMP Negeri 1 Lubuk Pakam - Nur Halimah; Abdul Hairuddin Angkat (PT FORMOSA CENDEKIA GLOBAL, 2023)
Iron deficiency anemia is a type of anemia case that is often found. During adolescence, the need for nutrients also increases, one of the nutrients whose needs increase is iron. Iron is needed by all body cells and is important for physiological processes such as the formation of hemoglobin (red blood cells) and enzyme function. The aim of the research was to determine the effect of counseling using animation media on increasing knowledge of anemia among young women at SMP Negeri 1 Lubuk Pakam. This research was conducted at SMP Negeri 1 Lubuk Pakam, Lubuk Pakam District, Deli Serdang Regency. Data collection was carried out from May 29 to June 12 2023. This research used a design commonly referred to as One Group Before After Intervention Design or One Group Pre and Post Test design which is part of a quasi-experimental design. The sample in this study was all anemic teenage students in class VIII at SMP Negeri 1 Lubuk Pakam who took part in the counseling from start to finish, namely 36 people. The data collected includes teenagers' knowledge about anemia using animation media. The average score obtained for a total of 36 grade 8 female students at SMP Negeri 1 Lubuk Pakam who took the pre-test was 8.78 with a standard deviation of 1.775. Meanwhile, the average knowledge score after counseling was 13.28 with a standard deviation of 1.137. There is a significant difference between education and animation media about anemia on knowledge. This is proven by a significant value of 0.00<0.05, so Ha is accepted.